Product Durability under Monopoly and Competition - Kamien, Morton I.; Schwartz, Nancy L. (Econometrica, 1974)
The durabilities of a consumption good produced in a perfectly competitive market or by a monopoly are compared. The analysis is conducted in terms of firm profit maximization in a Cournot industry. Conclusions are based on the properties of the entire optimal path rather than on the steady state alone.